PENDEKATAN BURHANI DALAM PEMENUHAN NAFKAH SKINCARE DAN KOSMETIK DALAM ISLAM - Alfikri, Ahmad Faiz Shobir; Soleh, Achmad Khudori; Wahda, Maziya Rahma (UIN Sunan Kalijaga Yogyakarta, 2024)
The wife's need for skincare and cosmetics has become the latest discourse in the framework of the fulfillment of maintenance by the husband to the wife. This study aims to examine the perspectives of classical and contemporary scholars on the fulfillment of skincare and cosmetic maintenance for wives in Islam and explore the use of burhani epistemology in reconstructing the law on the fulfillment of skincare and cosmetic maintenance. The method used in this research is library research with a descriptive-qualitative approach. The results of this study are (1) Skincare which is a necessity to maintain the cleanliness of the wife's skin so it must be fulfilled based on the agreement of the scholars of 4 madhhabs related to maintenance of body hygiene. However, the fulfillment of cosmetic nafkah is not mandatory, except in the Maliki school of thought, provided that the wife requires it; (2) The fulfillment of skincare and cosmetics maintenance by husbands can be analyzed using burhanu epistemology with the al-Qiyas al-Jam'i and tahlili methods. The al-Qiyas al-Jam'i method draws an analogy between basic needs and modern needs, while the tahlili method breaks down these elements for in-depth analysis of product halalness, health benefits, and psychological impact. With this burhani approach, the fulfillment of skincare and cosmetic needs is considered an integral part of the husband's maintenance responsibilities, supporting the wife's physical, mental and emotional well-being in accordance with maqasid sharia. Keywords: Burhani Epistemology; Nafkah; Skincare; Cosmetics. Kebutuhan istri akan skincare dan kosmetik menjadi diskursus terkini dalam kerangka pemenuhan nafkah oleh suami kepada isteri. Penelitian ini bertujuan untuk mengkaji perspektif ulama klasik dan kontemporer tentang pemenuhan nafkah skincare dan kosmetik bagi istri dalam Islam serta mengeksplorasi penggunaan epistemologi burhani dalam rekonstruksi hukum pemenuhan nafkah skincare dan kosmetik. Metode yang digunakan dalam penelitian ini adalah studi kepustakaan (library research) dengan pendekatan deskriptif-kualitatif. Hasil penelitian ini yaitu (1) Skincare yang merupakan kebutuhan untuk menjaga kebersihan kulit istri sehingga wajib dipenuhi berdasarkan kesepakatan ulama 4 mazhab berkaitan dengan nafkah kebersihan badan. Namun, pemenuhan nafkah kosmetik tidak wajib dipenuhi, kecuali dalam mazhab Maliki, dengan ketentuan apabila istri mensyaratkannya; (2) Pemenuhan nafkah skincare dan kosmetik oleh suami dapat dianalisis menggunakan epistemologi burhanu dengan metode al-Qiyas al-Jam’i dan tahlili. Metode al-Qiyas al-Jam’i menarik analogi antara kebutuhan dasar dan kebutuhan modern, sedangkan metode tahlili memecah elemen-elemen tersebut untuk analisis mendalam mengenai kehalalan produk, manfaat kesehatan, dan dampak psikologis. Dengan pendekatan burhani ini, pemenuhan kebutuhan skincare dan kosmetik dianggap sebagai bagian integral dari tanggung jawab nafkah suami, mendukung kesejahteraan fisik, mental, dan emosional istri sesuai dengan maqasid syariah. Kata kunci: Epistemologi Burhani; Nafkah; Skincare; Kosmetik